Analisis Kecelakaan Kapal Tubrukan Menggunakan Metode Human Factors Analysis And Classification System - Ingsun Sukmaya Datu; Marsha Anindya Jasmine; Miftakhul Jannah; Refani Naswa Salsabilla; Denny Oktavina Radianto (KOLONI, 2024)
Ships are a means of transportation that connects islands inside and outside the country's territory. Maritime workers are seafarers who are employed from various places and make various journeys to and from their homes. Since its founding, the International Maritime Organization (IMO) has attempted to reduce ship accidents by setting minimum safety standards for ships and their crews (Wahyuni ​​et al., 2021). As a result, accidents caused by technical or mechanical problems within the ship's structure are currently very low. However, human error is one of the most important sources of problems for the global maritime community. For example, Rothblum (2012) shows that human error accounts for more than 75% to 96% of marine accidents. Barsan, Surugiu, and Dragomir also show that more than 80% of maritime accidents are caused by human error (TRANSNAV, 2012). In carrying out this action, it is necessary to investigate the problem from which information can be drawn. So the method that will be used in this research is the HFACS method. Method (HFACS) is an accident analysis tool used to analyze Human Factors..